Leak test for solid oxide fuel cells and solid oxide electrolysis cells - Chou, Yeong-Shyung; Hardy, John; Marina, Olga A. (Frontiers in Energy Research, 2022)
This method provides a simple, fast, and economic way to assess if the seal of SOFC/SOEC cell to typical window frame plate is hermetic or not at room temperature using alcohol penetration. It al-so introduces methods to determine if the seal failed or cell cracked at high temperature after stack final firing either by with cross bubbling for unreduced cell or open circuit voltage (OCV) for full reduced cell.